Health-saving technologies in teacher’s activity //Tecnologías que promueven la salud en la actividad docente - Andrusova, Irina V.; Smirnova, Zhanna V.; Chelnokova, Elena A.; Nikeitseva, Olga N.; Tsaregorodtseva, Anna N. (Revista de la Universidad del Zulia, 2020)
Abstract The state, society and the labor market are making ever higher demands on teaching staff. Compliance with the established requirements forces students to increase energy consumption, the rate of development of the data, which entails a violation of biological rhythms, poor health and poor performance. Therefore, there is a need to improve the competencies of teachers related to mastering ways to improve the functional state and human health. The relevance of health-saving technologies implementation in vocational education is growing. Since there is no special course for their study, additional training courses on this topic become popular. Purpose of the article: designing the content of the course for additional professional training of teaching staff, ensuring the achievement of the development of health-saving technologies and their use in professional training. The aim of the course is to promote development of the competencies of teaching staff in the field of health-saving technologies application. The article reveals the possibilities of health-saving technologies, the role in preparation of an efficient, highly qualified specialist who meets modern requirements and is able to carry out professional activities at a high level. The study, in which experts selected from among the teachers of a higher educational institution, contributed to the solution of the problem of selecting the content of the course of additional professional training. When selecting the course content, an expert opinion on the established criteria was taken into account. As the planned results of the course, we determined a list of competencies that ensure the ability and willingness of teachers to systematically implement health-saving technologies. Resumen El Estado, la sociedad y el mercado laboral plantean cada vez más exigencias al profesorado. El cumplimiento de los requisitos establecidos obliga a los estudiantes a incrementar el consumo de energía, el ritmo de desarrollo de los datos, lo que conlleva una violación de los ritmos biológicos, mala salud y bajo rendimiento. Por tanto, existe la necesidad de mejorar las competencias de los docentes relacionados con el dominio de formas de mejorar el estado funcional y la salud humana. La importancia de la implementación de tecnologías que promueven la salud en la educación profesional está aumentando. Dado que no hay un curso especial para su estudio, los cursos de capacitación adicionales sobre este tema se vuelven populares. Objeto del artículo: diseñar el contenido del curso para la formación profesional adicional del profesorado, asegurando el logro del desarrollo de tecnologías promotoras de la salud y su uso en la formación profesional. El objetivo del curso es promover el desarrollo de las competencias del profesorado en el campo de la aplicación de tecnologías que promueven la salud. El artículo revela las posibilidades de las tecnologías promotoras de la salud, el papel en la preparación de un especialista eficiente y altamente calificado que cumpla con los requisitos modernos y sea capaz de realizar actividades profesionales de alto nivel. El estudio, en el que expertos seleccionados entre los profesores de una institución de educación superior, contribuyó a la solución del problema de selección del contenido del curso de formación profesional adicional. Al seleccionar el contenido del curso se tuvo en cuenta la opinión de un experto sobre los criterios establecidos. Como resultados planificados del curso, determinamos una lista de competencias que aseguran la capacidad y disposición de los docentes para implementar sistemáticamente tecnologías promotoras de la salud.